The theological wordbook the 200 most important theological terms and their relevance for today - Campbell, Donald K.; Swindoll, Charles R. 1934-; Zuck, Roy B. (Nashville, TN Word, 2000)
Includes bibliographicla references.
Keywords: Theology -- terminology; Bible -- theology